Communication-Based Health Service Policy for Optimizing Stunting Prevention Services at Kosiwo Health Center (Journal of Social And Education Research, 2024)
This study aims to analyze the relationship between communication-based health service policies and the optimization of stunting prevention services at Puskesmas Kosiwo, Yapen Islands Regency, Papua Province. The research employed an observational approach with a cross-sectional design involving 41 health workers selected through total sampling. Data were collected using a structured questionnaire that had been tested for validity and reliability, then analyzed using univariate and bivariate analyses with the chi-square test at a significance level of ? = 0.05. The results showed a significant relationship between communication-based health service policies and the optimization of stunting prevention services (p = 0.001). Health workers who applied active communication-based service policies achieved better optimization of stunting prevention efforts compared to those with passive approaches. The findings highlight that effective communication encompassing nutrition education, maternal counseling, interpersonal communication, intersectoral coordination, and media utilization plays a crucial role in improving the success of stunting prevention programs. Strengthening communication-oriented health policies is therefore essential to enhance service performance and accelerate stunting reduction efforts, especially in primary health care settings within remote regions such as Papua.